Telling the Prerrevolucionary Vieja Habana from City, Commerce, and Three Punctual Landmarks: Diamonds, the National City Bank, and the Revolution’s Arrival - Longan Phillips, Shirley (2022)
Received: 10-10-2021.Approved: 15-11-2021. Studying the History of La Vieja Habana prior to the Cuban Revolution is a challenge, not only in the country itself, but studying abroad. Ana Vera Estrada took this challenge and interviewed some elderly people, during the last months of 1999 and the first months of the year 2000. They draw, from their memories, the space called La Vieja Habana: its spatial and symbolic limits, the vivid commerce downtown, and specific moments of History that changed life before the Cuban Revolution in 1959: the diamonds industry and the National City Bank’s assault. This article takes as a basis Estrada’s text and makes an intertextual relation, to enhance by historiographic and bibliographical texts, the axes chosen from the oral stories recollected by Estrada.